Writing the TV drama series : how to succeed as a professional writer in TV - Douglas, Pamela, 1944- (Studio City Michael Wiese productions, 2018)
"Guide to writing drama series for TV, both in the US and in other countries" --
WHAT'S SO SPECIAL ABOUT TV DRAMA SERIES? -- HOW SHOWS GET ON TV AND THE TV SEASON -- HOW A CLASSIC SCRIPT IS CRAFTED -- WRITING YOUR OWN EPISODE -- IT'S WHO YOU KNOW: WORKING ON STAFF -- HOW TO BREAK IN -- PROFILES IN PROGRESS -- INTERNATIONAL TELEVISION -- THE FUTURE IS NOW.
Includes bibliographical references and index.
Keywords: Television authorship; Television series -- Authorship